DIGITAL MARKETING USAHA TOTEBAG BARCODE DALAM PENINGKATAN KAPABILITAS MAHASISWA MELALUI WIRAUSAHA MERDEKA - Viqie Aria Kusuma; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2025)
The eco-friendly totebag business is growing in response to the increasing awareness of the importance of reducing plastic waste (Zero Waste). This study explores the digital marketing for the Barcode totebag business using a SWOT analysis approach, aiming to improve students' capabilities through the Independent Entrepreneurship program. The main focus of this study is the importance of creativity, independence, and innovation in entrepreneurship for students, as well as business opportunities that arise from the increasing public awareness of a sustainable lifestyle. By utilizing creative designs and quality materials, this totebag business has the potential to attract consumer interest, especially among young people. SWOT analysis is used to identify strengths, weaknesses, opportunities, and threats, and to formulate effective marketing strategies to increase competitiveness and minimize risks. The Independent Entrepreneurship program supports the use of natural materials and traditional batik designs, which appeal to young consumers and increase customer loyalty. With effective marketing strategies, such as the use of social media and collaboration, this business has the potential to grow and provide valuable entrepreneurial experience for students. In conclusion, the Barcode Totebag business has significant growth potential with the implementation of the right marketing strategy.